Puroindoline (Pina-D1 and Pinb-D1) and waxy (Wx-1) genes in Iranian bread wheat (Triticum aestivum L.) landraces. Issue 1 (1st January 2020) - Maryami, Zahra; Azimi, Mohammad Reza; Guzman, Carlos; Dreisigacker, Sussane; Najafian, Godarz
Abstract: Grain hardness and starch are two of the most important factors that determine the end-use quality of bread wheat ( Triticum aestivum L.) grain. The grain hardness and amylose content are controlled by the puroindolines ( Pina-D1 and Pinb-D1 ) genes, located on chromosomes 5D, and waxy ( Wx-A1, -B1 and -D1 ) genes, located on chromosomes 7A, 4A and 7D. A total of 160 Iranian landraces from the Germplasm Bank of the International Maize and Wheat Improvement Center were evaluated for grain hardness using near infrared spectroscopy to predict the particle size index (PSI). In addition, molecular markers were used to evaluate the states of the corresponding genes. Eight accessions were found to have a hard texture (predicted PSI < 45%); however, only two could be explained by null alleles either in Pina-D1 or Pinb-D1 . Additionally, 152 accessions had semi-hard textures (predicted PSI range of 45% to 55%). For the Wx gene, only one accession (CWI 67665) showed the null Wx-D1b allele, while two accessions (CWI 67747 and CWI 57684) were null for Wx-B1b . Single nucleotide polymorphism and sequence tag site marker techniques were used. Our findings further indicate the importance of using these landraces for grain quality improvement in breeding programs.